Switzerland in perspective - Soloveytchik, George (Oxford University Press, 1954)
Books on Switzerland usually fall into teo clearly defined categories. Either they descibe the political institutions of the country but have little or nothing to say of its political life - which is a very different proposition - or else they are tourist books, describing the scenery, frequently relating details of personal experience, offering useful hints or warning to the discerning traveller, but in the course of all this saying not a word about the place tourism holds in Switzerland's own life.